MORFEM -KIRU SEBAGAI PENANDA ASPEK PERFEKTIF - Rini, Elizabeth Ika Hesti Aprilia Nindia (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2011)
Japanese aspect is marked lexically and grammatically. Lexically aspect is marked by the verb (動詞) and adverb (副詞). As aspect marker, there a derivative verb (派生動詞) and categories of verb (動詞 範疇性). Kiru as a morpheme is one of japanese aspect marker that formed by the process of derivation and has pervective meaning. And the type of verb that clung to the morpheme kiru will affect the meaning of the compound words.